THE TRANSFORMATION OF THE PARTAI KEADILAN SEJAHTERA: INCLUSIVITY IN INDONESIA’S MULTICULTURAL POLITICS - Ismed Kelibay; Haedar Nashir; Ridho Al-Hamdi; Masni Banggu (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2025)
This study analyzes the transformation of the Prosperous Justice Party (PKS) into an inclusive Islamic political party within Indonesia’s multicultural political landscape. Through an open political approach toward various groups, including non-Muslims, PKS demonstrates a significant strategic shift in its efforts to expand its mass base amid a plural society. Nonetheless, differences in perspectives within PKS have given rise to two main factions: the conservative Justice faction, which resists political compromise and emphasizes PKS’s identity as a dakwah-oriented party, and the more progressive Prosperity faction, which promotes party openness, supports pluralism, and encourages electoral modernization. This study applies Oliver Roy’s theory of political pragmatism in Islam, which posits a shift from an exclusive ideological orientation toward an inclusive and pragmatic political strategy. In this context, Islamism no longer focuses solely on rigid religious identity but transforms into a more pluralistic political movement that adapts to the parliamentary democratic system, emphasizing electoral strategies to broaden public support. The research employs a qualitative approach based on literature review and thematic interpretation. Findings indicate that PKS’s strategy reflects patterns of ideological adaptation by contextualizing Islamic values into universal issues, such as social justice, equality, anti-corruption, education, and welfare. The manifestation of this inclusive strategy is evident through the recruitment of members and the nomination of non-Muslim candidates, as well as the opening of political participation across religious lines. This adaptation does not aim to diminish PKS’s Islamic identity but rather reframes the party’s ideological message to align with the pluralistic, democratic, and pragmatic realities of Indonesian politics.